STUDI PEMANFAATAN METABOLIT SEKUNDER DALAM MASERAT Curcuma mangga Val. SEBAGAI INSEKTISIDA ALAMI - , ANGGRAENI DIAN P, Dra. Endang Astuti, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The study of insecticides potencies of the extract of Curcuma mangga Val. rhizomes that was obtained from several solvent with different polarity has been done. This study also aimed to identify the types and rates of flavonoid compounds and their effect on insecticides activities of Curcuma mangga Val. extract with different polarity. The study was divided into four steps. They were maceration of Curcuma mangga Val. rhizomes, the insecticide activity assay, phytochemical test, and separation of flavonoid compounds with Preparative Thin Layer Chromatography (PTLC). Maceration of Curcuma mangga Val. rhizomes was performed in solvents with increasing polarity namely petroleum ether, n-hexane, ethyl acetate, and ethanol. The insecticidal activity assay of Curcuma mangga Val. extract was tested againts Bactrocera carambolae at various concentration of samples, i.e. 37.5, 75, and 150 mg/mL. The phytochemical tests carried out this study were flavonoids, terpenoids, and alkaloid test. The insecticidal activities assay showed the highest declined mortality of petroleum ether extract, ethyl acetate extract, and ethanol extract was 7.67% (37.5 mg/mL), 30.22% (150 mg/mL), and 13.76% (75 mg/mL) respectively, while the n-hexane extract had not cause mortality in the test. The study showed that each of extract had different type and concentration of flavonoid compounds. Petroleum ether, n-hexane, ethyl acetate, and ethanol extract contain the concentration of flavonoid at 0.23%, 0.088%, 0.45%, and 1.34%, and contain the type of flavonoid were flavon and flavonol, flavon and flavonol, dihydrochalcon, chalcon and auron respectively. Therefore, it can be concluded that Curcuma mangga Val. extract had no potencies as insecticides against Bactrocera carambolae because the concentration of flavonoid compounds was low.